Frantschach Pulp & Paper : managing the transition from central planning to market economy - Nollen, Stanley D., (SAGE Knowledge. Cases., 2005)
Frantschach Pulp & Paper is a sizable Czech company that made the transition successfully from central planning to market economy. The case describes the company's problems and opportunities, focusing on the decisions made by its top management team. Frantschach suffered from deficient financial resources and faced the adversity of rogue investment funds as did many Czech companies, but overcame these problems in part with the help of foreign consultants, loans, and eventually foreign strategic investors. The central lesson to be learned from studying the case is to understand how Mr. Toma?s S?abatka, the managing director throughout the transition, was able to make the decisions that yielded a successful transition.